Square Grid Metal–Chloranilate Networks as Robust Host Systems for Guest Sorption. Issue 20 (13th March 2019) - Kingsbury, Christopher J.; Abrahams, Brendan F.; Auckett, Josie E.; Chevreau, Hubert; Dharma, A. David; Duyker, Samuel; He, Qilin; Hua, Carol; Hudson, Timothy A.; Murray, Keith S.; Phonsri, Wasinee; Peterson, Vanessa K.; et al.
Abstract: Reaction of the chloranilate dianion with Y(NO3 )3 in the presence of Et4 N + in the appropriate proportions results in the formation of (Et4 N)[Y(can)2 ], which consists of anionic square‐grid coordination polymer sheets with interleaved layers of counter‐cations. These counter‐cations, which serve as squat pillars between [Y(can)2 ] sheets, lead to alignment of the square grid sheets and the subsequent generation of square channels running perpendicular to the sheets. The crystals are found to be porous and retain crystallinity following cycles of adsorption and desorption. This compound exhibits a high affinity for volatile guest molecules, which could be identified within the framework by crystallographic methods. In situ neutron powder diffraction indicates a size‐shape complementarity leading to a strong interaction between host and guest for CO2 and CH4 . Single‐crystal X‐ray diffraction experiments indicate significant interactions between the host framework and discrete I2 or Br2 molecules. A series of isostructural compounds (cat)[M III (X‐an)2 ] with M=Sc, Gd, Tb, Dy, Ho, Er, Yb, Lu, Bi or In, cat=Et4 N, Me4 N and X‐an=chloranilate, bromanilate or cyanochloranilate bridging ligands have been generated. The magnetic properties of representative examples (Et4 N)[Gd(can)2 ] and (Et4 N)[Dy(can)2 ] are reported with normal DC susceptibility but unusual AC susceptibility data noted for (Et4 N)[Gd(can)2 ]. Abstract : An extensive family of square grid anionic coordination polymers is formed by the combination of 8‐coordinate trivalent metal ions with bridging chloranilate ligands. Alignment of the square grid networks produces channels that are able to accommodate a variety species. The location of guest molecules within the channels has been determined using both X‐ray and neutron diffraction.